NATURAL GERMINATION AS RESILIENCE COMPONENT IN MEDITERRANEAN COPPICE STANDS OF CASTANEA-SATIVA MILL AND QUERCUS-ILEX L (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 1994)
In the Mediterranean basin, most of the present forests derive from original forests where the dominant species was different from the present one. These changes are largely due to human activities reflecting millenia of management and, often, overexploitation. In southern France, for example, palaeoecologists believe that the original malacophyllous deciduous forest of downy oak (Quercus pubescens) was replaced by a sclerophyllous evergreen holm oak (Quercus ilex) coppice in the driest areas, and chestnut (Castanea sativa) orchards or coppices in the `'wettest'' areas. However, for the last several decades, exploitation of these coppice stands has been decreasing. In this study, we addressed the question of the resilience of these managed ecosystems in the fact of changing management schemes, and to determine appropriate strategies and criteria of sustainable development. We present some aspects of the auto-succession after clearcutting of holm oak coppice stands and aspects of the natural regeneration of 4 species (Q. ilex, Q. pubescens, C. sativa, and P. pinaster). The consequences of the contrasted life history strategies are compared to estimate the future of these coppices.

Germination and regeneration mechanisms in Mediterranean degenerate forests (Journal of Vegetation Science, 1993)
Abstract. Germination and developmental behaviour during juvenile stages are of importance in relation to succession mechanisms acting on plant communities. This is particularly so in the Mediterranean region, where the climatic summer drought causes stress. We investigated and compared germination and development of four tree species in two parts of the French Mediterranean region where the original dominant tree species (Quercus pubescens) has been largely replaced by Quercus ilex in the southern part, and Castanea sativa in the northern part. Observed differences in germination rates and developmental behaviour, especially shootroot ratio and the role of water supply, suggest that other species may eventually replace the current dominant species.

Germination of Quercus ilex and Q. pubescens in a Q. ilex coppice (Plant Ecology, 1990)
Quercus ilex L. (holm oak) coppices, widespread around the Mediterranean basin, are probably the result of 5 000 years of prolonged human disturbance of the original Quercus pubescens Willd. (downy oak) forests. Since disturbance has almost ceased in recent years, a question arises as to the development of these coppices: will the Q. pubescens forests return, or will Q. ilex remain the dominant species? To investigate the phenomenon, we analyzed the first stages, i.e. germination of the two species in holm oak coppices. Our experiments show that both species germinated better in coppices than in clearings or clear-cuts. Moreover, Q. pubescens appears to be slightly favored above Q. ilex and it is suggested auto-allelopathy is involved, at least partially inhibiting the germination of Q. ilex.